2016
DOI: 10.1186/s12962-016-0057-0
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ willingness to pay for HPV vaccines in Anambra state, Nigeria: a cross sectional contingent valuation study

Abstract: BackgroundHuman papilloma virus (HPV) vaccination in Nigeria will require substantial financing due to high cost of HPV vaccine and inexistence of structures to support adolescent vaccination. Alternative sources are needed to sustain the government funded HPV vaccination programme. This study assessed Nigerian mothers’ willingness-to-pay (WTP) for HPV vaccine. We also compared the difference between the average WTP and estimated costs of vaccinating a pre-adolescent girl (CVG).MethodsWe conducted a quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 14 publications
2
46
2
1
Order By: Relevance
“…This may be due to population difference, the currency inflation, differences in preventive health services studied and the target population appreciation of the usefulness or importance of different preventive health services. However, the result of this study was lower than a study done on WTP for HPV vaccine which was US$ 11.68 in Nigeria [17] and US$ 50.26 in Malaysia [18], and WTP for the clinical preventive services which was US$ 93.72 in South Nigeria [19]. This may be due to differences in socio-status of study participants and program preference.…”
Section: Discussioncontrasting
confidence: 73%
“…This may be due to population difference, the currency inflation, differences in preventive health services studied and the target population appreciation of the usefulness or importance of different preventive health services. However, the result of this study was lower than a study done on WTP for HPV vaccine which was US$ 11.68 in Nigeria [17] and US$ 50.26 in Malaysia [18], and WTP for the clinical preventive services which was US$ 93.72 in South Nigeria [19]. This may be due to differences in socio-status of study participants and program preference.…”
Section: Discussioncontrasting
confidence: 73%
“…The possible explanation for this may be study population difference, the currency inflation and program differences. But the result of the study was lower than a study done on willingness to pay for HPV vaccine which was US$ 11.68 in Nigeria [16] and US$ 50.26 in Malaysia [17], and WTP for the clinical preventive services which was US$93.72 in South-Nigeria [18]. This may be due to the difference in socioeconomic difference of the participants like per capita income, study population difference.…”
Section: Discussionmentioning
confidence: 65%
“…27 In the context of human papillomavirus vaccine, a study in Nigeria found that vaccine price and experienced illness influenced WTP. 28 In Thailand, analyses of interviews with 2693 respondents demonstrated that attitude toward vaccination, knowledge, history of receiving vaccination, and educational Figure 1. Correlation model between socioeconomic status, knowledge on dengue fever, attitude toward dengue fever, practice on dengue prevention, attitude toward vaccination, dengue vaccine acceptance and willingness to pay for dengue vaccine.…”
Section: Factors Associated With Willingness To Pay For Dengue Vaccinementioning
confidence: 99%